Effect of ecological restoration on physicochemical properties, bacterial and fungal communities of red sand soil in Longquan Mountain forest park - Yan Wang; Yu-Long Zhang; Rui Zhang; Cai-Xia Li; Xian-Jun Lai; Xin-Rong Ma (Ecological Indicators)
Longquan Mountain, located east of the Chinese city of Chengdu, is characterized by a barren red sand soil. For the construction of Longquan Mountain Forest Park, ecological restoration was carried out, which involved mixing pastoral soil and biochar into the milled shale, introducing earthworms, and phytoremediation. This study examined changes in the physicochemical properties and microbial communities of soils through ecological restoration. There was a significant increase in organic matter, total phosphorus, available iron, and total nitrogen, as well as a notable decrease in soil calcium content, resulting in a substantial enhancement of soil quality. Ecological restoration significantly optimized the community structure and diversity of bacteria, but with minor shifts in the composition and structure of fungi. Verrucomicrobia, Chloroflexi, Acidobacteria, and Planctomycetes were enriched in restored soils and functioned in the hydrolysis of polysaccharides and organic acids, as well as in the degradation of plant residues, plant-derived polymers, and bacterial-derived exopolysaccharides. Another dominant bacterium in the restored soil, Gemmatimonadetes, may have contributed to the soil’s adaptation to the seasonally dry environment of the restoration area. In addition, fungi may participate in ecological restoration activities by assisting bacteria, particularly Sordariales, which were once decomposers of decaying matter. Interactions between soil microorganisms, plants and soil nutrients have transformed Longquan Mountain’s ecosystem into a virtuous cycle, with survival rates of vegetation reaching more than 90 percent after two years and significant reductions in harmful substances in the soil. This study provides both a theoretical basis and an engineering demonstration for ecological restoration efforts in degraded or poor soils.